PENGARUH PEMBELAJARAN DARING TERHADAP HASIL BELAJAR DESAIN GRAFIS SISWA DI SMK - Alfrina Mewengkang; Cliferd Osaka Najoan; Verry Ronny Palilingan; Viktory Nicodemus Joufree Rotty; Jeffry Sonny Lengkong; Harold Refli Lumapow (Lembaga Penelitian dan Pendidikan Mandala, 2022)
The development of technology in the field of education is seen very rapidly and has produced many new learning methods and models that are used to compete in the world of education in producing quality human resources and being able to compete in the industrial world or the world of work. However, since the world was hit by the COVID-19 pandemic, the government, especially in the field of education, suggested that every school use online learning methods with the aim of breaking the chain of the spread of COVID-19. The purpose of this research is to see if there is an effect of online learning on student learning outcomes in graphic design subjects at SMK Eklesia Jailolo. The results showed that the online learning method with the Project Based Learning (PjBL) learning model was higher than online learning with the conventional learning model (lectures). Keywords: